Three‐dimensional printed polycaprolactone‐microcrystalline cellulose scaffolds. Issue 3 (2nd May 2018) - Alemán‐Domínguez, Maria Elena; Giusto, Elena; Ortega, Zaida; Tamaddon, Maryam; Benítez, Antonio Nizardo; Liu, Chaozong
Abstract: Microcrystalline cellulose (MCC) is proposed in this study as an additive in polycaprolactone (PCL) matrices to obtain three‐dimensional (3D) printed scaffolds with improved mechanical and biological properties. Improving the mechanical behavior and the biological performance of polycaprolactone‐based scaffolds allows to increase the potential of these structures for bone tissue engineering. Different groups of samples were evaluated in order to analyze the effect of the additive in the properties of the PCL matrix. The concentrations of MCC in the groups of samples were 0, 2, 5, and 10% (w/w). These combinations were subjected to a thermogravimetric analysis in order to evaluate the influence of the additive in the thermal properties of the composites. 3D printed scaffolds were manufactured with a commercial 3D printer based on fused deposition modelling. The operation conditions have been established in order to obtain scaffolds with a 0/90° pattern with pore sizes between 450 and 500 µm and porosity values between 50 and 60%. The mechanical properties of these structures were measured in the compression and flexural modes. The scaffolds containing 2 and 5% MCC have higher flexural and compression elastic modulus, although those containing 10% do not show this reinforcement effect. On the other hand, the proliferation of sheep bone marrow cells on the proposed scaffolds was evaluated over 8 days. The results show that the proliferation is significantly better ( p  < 0.05) on the group of samples containing 2% MCC. Therefore, these scaffolds (PCL:MCC 98:2) have suitable properties to be further evaluated for bone tissue engineering applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 521–528, 2019.